2013
DOI: 10.1111/j.1464-410x.2012.11763.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoendoscopic single site (LESS) and conventional laparoscopic donor nephrectomy at a single institution

Abstract: • Most transplant centres harvest living donor kidneys via a conventional laparoscopic surgical approach.Laparoendoscopic single-site donor nephrectomy (LESS-DN) is a relatively novel minimally invasive approach that allows the surgery to be performed via a single incision. This technique may be advantageous in decreasing surgical morbidity and improving cosmetic outcomes, thus plausibly reducing the barriers to kidney donation.• The study demonstrates the safety and feasibility of LESS-DN in a large consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…The majority of the studies described the evolution from ODN to LDN (22 studies). A few studies described the adaptation of retroperitoneal laparoscopic techniques, whereas five studies reported on the introduction of single‐incision laparoscopic techniques . Horgan et al.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies described the evolution from ODN to LDN (22 studies). A few studies described the adaptation of retroperitoneal laparoscopic techniques, whereas five studies reported on the introduction of single‐incision laparoscopic techniques . Horgan et al.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to cosmetic advantages, patients may experience less postoperative pain and fewer port site‐related complications. Several institutions have reported using LESS for live donor nephrectomy (LESS‐DN) and other therapeutic/reconstructive renal procedures, showing similar perioperative outcomes and equivalent complication rates, with varying results related to donor recovery and cosmesis . Meta‐analysis of 27 studies comparing LESS versus laparoscopic nephrectomy in patients undergoing radical or partial nephrectomy for cancer, donor nephrectomy or mixed procedures found LESS to be a safe and effective alternative with potential benefits of reduced pain, shorter recovery and improved cosmesis .…”
Section: Introductionmentioning
confidence: 99%
“…Key words: Cholecystectomy; laparoscopy; single-incision laparoscopic surgery (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%